The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1997
DOI: 10.1046/j.1365-2265.1997.2201033.x
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative tetany in patients with Graves' disease: a risk factor analysis

Abstract: These results, combined with previous observations in which a significant decline in serum parathyroid hormone level was found in patients with Graves' disease who suffered postoperative tetany, suggests that postoperative tetany may occur during the period of bone restoration due to antithyroid drug therapy and be due to continuation of a calcium flux bone concomitant with transient hypoparathyroidism induced by surgery. Calcium supplements during preoperative period and/or after surgery may be appropriate fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
2
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 16 publications
1
37
2
2
Order By: Relevance
“…In previous studies we have shown that postoperative tetany occurs in patients with secondary hyperparathyroidism caused by deficiencies in calcium and vitamin D due to increased demand for bone restoration after medical therapy concomitant with hypoparathyroidism after surgery [1][2][3][4].…”
Section: Thyroidectomymentioning
confidence: 99%
“…In previous studies we have shown that postoperative tetany occurs in patients with secondary hyperparathyroidism caused by deficiencies in calcium and vitamin D due to increased demand for bone restoration after medical therapy concomitant with hypoparathyroidism after surgery [1][2][3][4].…”
Section: Thyroidectomymentioning
confidence: 99%
“…29,30 In contrast, a large body of literature reports that female sex is associated with a significantly higher incidence of hypocalcemia compared with males. 20,24,27,28,3134 In our study, 76% and 79% of patients who developed postoperative mild and significant hypocalcemia were female ( P = .003), respectively, and male sex was found to be independently protective against postoperative hypocalcemia.…”
Section: Discussionmentioning
confidence: 44%
“…A small number of studies have found hypocalcemia to be associated with advanced age, 15,2325 whereas others have reported an association with younger age. 2628 A recent meta-analysis by Edafe et al 20 evaluated age as a predictor of hypocalcemia in 2576 patients and found no significant difference in mean age between patients with hypocalcemia and those without. Conversely, in our study we observed that patients who developed postoperative mild and significant hypocalcemia were a mean of 1 and 5 years younger than patients who did not ( P = .02).…”
Section: Discussionmentioning
confidence: 99%
“…Since the number of parathyroid glands identified was actually higher in the GO group than in the non-GO group, it was not related to identifying the parathyroids but rather related to preserving the blood supply to the parathyroids. The second explanation for the higher incidence of hypoparathyroidism in GO might be related to the phenomenon of “hungry bone” syndrome after surgery as reported previously in GD after thyroidectomy [25]. Perhaps patients with active GO might have a more severe form of hungry bone syndrome.…”
Section: Discussionmentioning
confidence: 83%